2022
DOI: 10.1097/corr.0000000000002374
|View full text |Cite
|
Sign up to set email alerts
|

Do Americans Lacking a Local Orthopaedic Surgeon Have Adequate Broadband for Telehealth?

Abstract: Background Although telehealth holds promise in expanding access to orthopaedic surgical care, high-speed internet connectivity remains a major limiting factor for many communities. Despite persistent federal efforts to study and address the health information technology needs of patients, there is limited information regarding the current high-speed internet landscape as it relates to access to orthopaedic surgical care. Questions/purposes (1) What is the distribution of practicing orthopaedic surgeons in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In a study by Jella et al [4] in this month’s Clinical Orthopaedics and Related Research ® , the authors used the Federal Communications Commission Mapping Broadband in America interactive tool to investigate the presence of broadband internet access regarding the distribution of practicing orthopaedic surgeons in the United States, as well as the geographic, demographic, and socioeconomic factors associated with the absence of high-speed internet and access to a local orthopaedic surgeon. Interestingly, the authors found that 14% of United States counties were considered “low-access” areas, meaning that the counties had no local orthopaedic surgeon and fewer than 50% of residents had broadband access.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Jella et al [4] in this month’s Clinical Orthopaedics and Related Research ® , the authors used the Federal Communications Commission Mapping Broadband in America interactive tool to investigate the presence of broadband internet access regarding the distribution of practicing orthopaedic surgeons in the United States, as well as the geographic, demographic, and socioeconomic factors associated with the absence of high-speed internet and access to a local orthopaedic surgeon. Interestingly, the authors found that 14% of United States counties were considered “low-access” areas, meaning that the counties had no local orthopaedic surgeon and fewer than 50% of residents had broadband access.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…This heatmap represents broadband internet access across the 1021 United States counties without access to a local orthopaedic surgeon. Reprinted with permission from Jella et al [4]. …”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation